The influence of academic leadership styles on school culture within secondary resource schools in Cambodia - Sreytouch Chamraeun; Sarom Mok; Mengheang Hor; Ramy Chhun; Sereyrath Em (Journal of General Education and Humanities, 2026)
In Cambodia, Secondary Resource Schools (SRSs) serve a unique purpose that extends beyond academic success to encompass the fostering of character development and spiritual growth. Understanding academic leadership practices is especially important due to the dual focus on academic and spiritual outcomes, as these leaders create the conditions for both cognitive and spiritual development. Given its importance, the fundamental purpose of this study was to explore how academic leadership styles (instructional and servant) influence the internal culture of the SRSs in Cambodia. To collect survey data from 150 teachers at SRSs in Cambodia, this study used a quantitative approach. The Principal Instructional Management Rating Scale (PIMRS), the Servant Leadership Questionnaire (SLQ), and the School Culture Survey (SCS) are well-known tools for assessing servant leadership, instructional leadership, and school culture. Their validation in earlier research ensures the applicability of these instruments to the goals of this study. The study's results demonstrate that instructional and servant leadership have a significant influence on school culture in SRSs in Cambodia. While instructional leadership had a stronger influence on academic and professional growth, servant leadership had a statistically significant influence on aspects of community and collaboration. Each of the two leadership styles had a more noticeable impact on distinct facets of school culture. The study’s conclusions point to several tactical methods for implementing effective leadership practices in SRSs in Cambodia. Based on these findings, conclusions and recommendations for future research are provided.